Assessment of motion of colonic contents in the human colon using MRI tagging - Pritchard, Susan E.; Paul, J.; Major, Giles; Gowland, Penny A.; Spiller, Robin C.; Hoad, Caroline (Wiley, 2017)
Background We have previously reported a non-invasive, semi-automated technique to assess motility of the wall of the ascending colon (AC) using Magnetic Resonance Imaging. This study investigated the feasibility of using a tagged MRI technique to visualise and assess the degree of flow within the human ascending colon in healthy subjects and those suffering from constipation. Methods An open-labelled study of 11 subjects with constipation and 11 subjects without bowel disorders was performed. MRI scans were acquired fasted, then 60 and 120 mins after ingestion of a 500ml macrogol preparation. The amount of free fluid in the small and large bowel was assessed using a heavily T2-weighted MRI sequence. The internal movement of the contents of the AC were visualised using a cine tagged MRI sequence and assessed by a novel analysis technique. Comparisons were made between fasting and postprandial scans within individuals, and between the constipation and control groups. Key results. Macrogol significantly increased the mobile, MR visible water content of the ascending colon at 60 mins post ingestion compared to fasted data (controls p=0.001, constipated group p=0.0039). The contents of the AC showed increased motion in healthy subjects but not in the constipated group with significant differences between groups at 60 minutes (p<0.002) and 120 minutes (p<0.003). Conclusions and inferences. This study successfully demonstrated the use of a novel MRI tagging technique to visualise and assess the motion of ascending colon contents following a 500ml macrogol challenge. Significant differences were demonstrated between healthy and constipated subjects.